Doxorubicin-loaded polypyrrole nanovesicles for suppressing tumor metastasis through combining photothermotherapy and lymphatic system-targeted chemotherapy. Issue 8 (10th February 2022) - Wang, Lu; Liu, Genhua; Hu, Yunping; Gou, Shuangquan; He, Tingting; Feng, Qian; Cai, Kaiyong
Abstract : Polypyrrole nanovesicles (PPy NVs) with hydrodynamic diameters of around 28 nm and negatively-charged surface have been prepared for combined photothermal therapy and lymphatic targeting chemotherapy to inhibit tumor metastasis. Abstract : The lymphatic system provides a main route for the dissemination of most malignancies, which was related to high mortality in cancer patients. Traditional intravenous chemotherapy is of limited effectiveness on lymphatic metastasis due to the difficulty in accessing the lymphatic system. Herein, a novel lymphatic-targeting nanoplatform is prepared by loading doxorubicin (DOX) into sub-50 nm polypyrrole nanovesicles (PPy NVs). The PPy NVs possessed hollow spherical morphologies and a negative surface charge, leading to high drug loading capacity. These vesicles can also convert near-infrared (NIR) light into heat and thus can be used for tumor thermal ablation. DOX loaded PPy NVs (PPy@DOX NVs) along with NIR illumination are highly effective against 4T1 breast cancer cells in vitro . More importantly, following subcutaneous (SC) injection, a direct lymphatic migration of PPy@DOX NVs is confirmed through fluorescence observation of the isolated draining nodes. The acidic conditions in metastatic nodes might subsequently trigger the release of the encapsulated DOX NVs based on their pH-sensitive release profile. In a mouse model bearing 4T1 breast cancer, lymphatic metastases, as well as lung metastases, are significantly inhibited by nanocarrier-mediated trans-lymphatic drug delivery in combination with photothermal ablation. In conclusion, this platform holds great potential in impeding tumor growth and metastasis.